Evaluation of positive emotion in children mobile learning application - Magrizef Gasah; Aslina Baharum; Nurul Hidayah Mat Zain; Suhaida Halamy; Rozita Hanapi; Noorsidi Aizuddin Mat Noor (Bulletin of Electrical Engineering and Informatics, 2020)
This paper presents the evaluation of positive emotion in children's mobile learning applications. The mobile learning application is a teaching aid that can help students to self-study and increase the students’ interest in learning especially children. This paper will discuss how mobile learning application affects the children interest in school. The evaluation method implemented to evaluate the rate of positive emotion elicited by the children using mobile learning applications was a mixed method of qualitative and quantitative methods. Since emotion can be either negative or positive, the identification of a proper method or perspective was required to prove that positive emotion was really elicited. Next, the data was collected through the children’s assessment score, Electroencephalograms (EEG) device, Emotion identification using micro-expression (facial expression), Kort Scale and interview to confirm the positive emotion felt by the students. The result shows that all five perspectives or methods have shown that positive emotion is produced. It is found that the Mobile learning application can really trigger the children’s positive emotions.